Meningkatkan Kebugaran Jasmani Menggunakan Permainan pada Siswa Kelas VI Sekolah Dasar Negeri 2 Pojok Kota kediri - Bima Kukuh Dwi Pamungkas; Moh. Nur Kholis; A. Zakiyyunnuhaa Fishilia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Sports lessons are primarily part of the entire education system. The purpose of sports education is not only in the physical domain, but also aspects of health, physical form, skills for critical thinking, emotional stability, social skills, discussion, and ethical behavior through physical and sports activities. Sports lessons give students the opportunity to participate in a systematic, oriented, planned learning experience through physical activity, games and systematic movements. Based on the above explanation, the author conducted a study on improving the title of physical forms by relying on micro-class students to study physical education at Koljok 2 Elementary School in Kediri city. This research was conducted as educational research (Classic Action Research). The test results for February 19, 2025 after learning using the game approach, the results in cycle I for male students increased to 2.15